Farquharson's textbook of operative general surgery [ - Farquharson, Eric L. [ (Eric Leslie)]; Farquharson, Margaret; Moran, Brendan (United States of America by Oxford University, 2005)
First published in 1954, Farquharson's Textbook of Operative General Surgery has become firmly established as a classic textbook for trainee surgeons throughout the world. Basic surgical techniques, including the reasons for their application, are discussed. General surgical operations are described and the indications for them are covered. Techniques are described in sufficient detail to allow a surgeon who has limited experience of a particular operation to proceed with confidence and safety.